Sorghum Silage Cost-Return Budget in South Central Kansas - Warmann, Gerald W. (My University, 1999)
The cost-return projection estimates the cost of producing forage sorghum silage in south central Kansas.
MF648_1999_10
Keywords: MF648; Economics; Crops; MF